ANALISIS DAMPAK KENAIKAN PAJAK PERTAMBAHAN NILAI (PPN) TERHADAP OMSET PENJUALAN PADA PT. RODA MAS AUTO PRIMA - Fitriani Lubis, Ayu; Siregar, Lukman Hakim; Nurhayati, Nurhayati (Jurnal Manajemen Akuntansi dan Ilmu Ekonomi, 2025)
This study analyses the impact of the Value Added Tax (VAT) rate increase from 10% to 11% that came into effect in April 2022 on sales turnover at PT Roda Mas Auto Prima, an automotive repair shop in Medan. This VAT increase is a strategic government policy to strengthen state revenue and overcome the budget deficit due to the COVID-19 pandemic. The research uses a qualitative descriptive method with data collection techniques through observation, in-depth interviews, and documentation of company financial data for 2021, 2022, and 2023. The analysis was conducted through a comparison of turnover data before and after the VAT increase and a narrative review of the company's adaptation strategy. The results showed that the turnover of PT Roda Mas Auto Prima experienced growth despite the VAT rate increase, from IDR 3.86 billion in 2021 to IDR 4.80 billion in 2022 and jumped to IDR 7.10 billion in 2023. The determining factor for success lies not only in adjusting prices after the VAT increase, but also in service innovation, improving work quality, and promotion and discount strategies to maintain customer loyalty. This research shows that with the right adaptive measures, companies can overcome the challenges of fiscal policy changes and maintain business growth. This study serves as a valuable reference for automotive businesses and fiscal policy stakeholders in the future.